Is inhibition implemented during bilingual production and comprehension? n-2 language repetition costs unchained. Issue 5 (28th May 2018) - Declerck, Mathieu; Philipp, Andrea M.
ABSTRACT: Many models assume that inhibition plays an integral role during bilingual language control, a process that restricts bilingual language processing to the target language. However, there is limited evidence for such a claim. In the current study, we set out to investigate one known marker of bilingual inhibition (n-2 language repetition costs) that has, so far, mainly been investigated with digits in a production task. Hence, we ran a n-2 language repetition study with other types of stimuli (i.e. pictures and written words) in a production and a comprehension task. The results showed that n-2 language repetition costs were found with both stimulus types in a production task. In the comprehension tasks, n-2 language repetition costs were only observed with one of the two stimulus types and in only one language. These results indicate that inhibition is implemented during bilingual production, and is possible, but not necessary, during bilingual comprehension.